Is catheter ablation associated with preservation of cognitive function? An analysis from the SAGE-AF observational cohort study - Srichawla, Bahadar S.; Hamel, Alexander P.; Cook, Philip; Aleyadeh, Rozaleen; Lessard, Darleen; Otabil, Edith M.; Mehawej, Jordy; Saczynski, Jane S.; McManus, David D.; Moonis, Majaz (Frontiers in Neurology, 2024)
Objectives: To examine the associations between catheter ablation treatment (CA) versus medical management and cognitive impairment among older adults with atrial fibrillation (AF).: Ambulatory patients who had AF, were ≥ 65-years-old, and were eligible to receive oral anticoagulation could be enrolled into the SAGE (Systematic Assessment of Geriatric Elements)-AF study from internal medicine and cardiology clinics in Massachusetts and Georgia between 2016 and 2018. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) tool at baseline, one-, and two years. Cognitive impairment was defined as a MoCA score ≤ 23. Multivariate-adjusted logistic regression of longitudinal repeated measures was used to examine associations between treatment with CA vs. medical management and cognitive impairment.Results: 887 participants were included in this analysis. On average, participants were 75.2 ± 6.7 years old, 48.6% women, and 87.4% white non-Hispanic. 193 (21.8%) participants received a CA before enrollment.Participants who had previously undergone CA were significantly less likely to be cognitively impaired during the two-year study period (aOR 0.70, 95% CI 0.50-0.97) than those medically managed (i.e., rate and/or rhythm control), even after adjusting with propensity score for CA. At the two-year follow-up a significantly greater number of individuals in the non-CA group were cognitively impaired (MoCA ≤ 23) compared to the CA-group (311 [44.8%] vs. 58 [30.1%], p=0.0002).In this two-year longitudinal prospective cohort study participants who underwent CA for AF before enrollment were less likely to have cognitive impairment than those who had not undergone CA.